Diagnostic Accuracy of the Xpert MTB/RIF Assay for Extrapulmonary Tuberculosis in Children With Musculoskeletal Infections. Issue 11 (November 2016) - Held, Michael; Laubscher, Maritz; Mears, Stewart; Dix-Peek, Stewart; Workman, Lesley; Zar, Heather; Dunn, Robert
Abstract : Background: Xpert MTB/RIF (Xpert) is useful for the diagnosis of extrapulmonary tuberculosis (TB) in adults, but there is limited evidence on its usefulness in children. We aimed to investigate the accuracy of Xpert for the diagnosis of extrapulmonary TB in children with musculoskeletal infections. Methods: The diagnostic accuracy of Xpert was compared with a reference standard of culture or histopathology in children hospitalized with suspected osteoarticular TB in Cape Town, South Africa from June 2013 to May 2015. Results: One hundred and nine samples of 102 patients (60 male; 58.8%) with a median age of 5.6 years (interquartile range: 2.2–8.7) were included. There were 23 samples with confirmed TB by culture or histology (21.1%); histology was positive in all of these, while culture was positive in 14 samples (12.8%). Xpert was positive in 17 samples (15.6%), providing a sensitivity of 73.9% (95% confidence interval: 51.6–89.8) and specificity of 100% (95% confidence interval: 95.7–100). Xpert was positive at a mean of 0.8 days (0.46–1.4) compared with 21 days (19–30) for culture, P < 0.001. Multidrug-resistant TB was detected on culture in a single sample that was negative on Xpert testing. Conclusions: Xpert confirmed extrapulmonary TB of bone and joints more accurately and faster than culture and should be used as a first-line test. Histology remains a useful test for musculoskeletal TB in children.